2017
DOI: 10.1186/s12934-017-0742-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression and secretion of fungal endoglucanase II and chimeric cellobiohydrolase I in the oleaginous yeast Lipomyces starkeyi

Abstract: Background Lipomyces starkeyi is one of the leading lipid-producing microorganisms reported to date; its genetic transformation was only recently reported. Our aim is to engineer L. starkeyi to serve in consolidated bioprocessing (CBP) to produce lipid or fatty acid-related biofuels directly from abundant and low-cost lignocellulosic substrates.ResultsTo evaluate L. starkeyi in this role, we first conducted a genome analysis, which revealed the absence of key endo- and exocellulases in this yeast, prompting us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 76 publications
2
16
0
Order By: Relevance
“…Yeast strains were grown in YPD at 30 °C (with shaking at 220 rpm) for general growth and transformation unless noted. The Gibson Assembly Cloning Kit (NEB, Ipswich, MA, USA) was used to insert target genes into vectors [ 16 ] and then followed by standard gene cloning protocols [ 30 ]. The primers and plasmids used in this study are listed in Additional files 1 and 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Yeast strains were grown in YPD at 30 °C (with shaking at 220 rpm) for general growth and transformation unless noted. The Gibson Assembly Cloning Kit (NEB, Ipswich, MA, USA) was used to insert target genes into vectors [ 16 ] and then followed by standard gene cloning protocols [ 30 ]. The primers and plasmids used in this study are listed in Additional files 1 and 2 , respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Lipomyces starkeyi NRRL Y-11557 was acquired from the ARS Culture Collection (NRRL) and was transformed following the optimized transformation protocol as described [ 31 ] and modified by Xu et al [ 16 ]. Briefly, cells were grown to an OD 600 of approximately 10.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The enzyme displayed its maximum activity at a temperature of 50 °C and a pH value of 5.0. This enzyme is highly stable in a pH range from 4.0 to 7.0 and at NaCl concentrations up to 3.0 M. Xu et al 21 reported the expression and secretion of fungal endoglucanase II and chimeric cellobiohydrolase I in the oleaginous yeast Lipomyces starkeyi and the authors demonstrated that the engineered L. starkeyi was capable of expressing and secreting both enzymes with high activity toward cellulose.…”
Section: Introductionmentioning
confidence: 99%